Cloning and phylogenetic analysis of NMDA receptor subunits NR1, NR2A and NR2B in Xenopus laevis tadpoles - Ewald, Rebecca C.; Cline, Hollis (Frontiers in Molecular Neuroscience, 2009)
N-methyl-D-aspartate receptors (NMDARs) play an important role in many aspects of nervous system function such as synaptic plasticity and neuronal development. NMDARs are heteromers consisting of an obligate NR1 and most commonly one or two kinds of NR2 subunits. While the receptors have been well characterized in some vertebrate and invertebrate systems, information about NMDARs in Xenopus laevis brain is incomplete. Here we provide biochemical evidence that the NR1, NR2A and NR2B subunits of NMDARs are expressed in the central nervous system of X. laevis tadpoles. The NR1-4a/b splice variants appear to be the predominant isoforms while the NR1-3a/b variants appear to be expressed at low levels. We cloned the X. laevis NR2A and NR2B subunits and provide a detailed annotation of their functional domains in comparison with NR2A and NR2B proteins from 10 and 13 other species, respectively. Both NR2A and NR2B proteins are remarkably well conserved between species, consistent with the importance of NMDARs in nervous system function.